Living-apart-together (LAT) relationships in Australia - Evans, A; Reimondos, A; Gray, E (My University, 2011)
Contemporary research on the nature and pattern of relationship formation and dissolution has almost exclusively focused on unions such as cohabitation and marriage in which the two partners share a common household. However, changing demographic trends mean that a substantial proportion of the population does not live with a romantic partner. In this paper, the authors describe the characteristics of individuals in non-residential unions and investigate whether these unions are a stepping stone towards cohabitation, or whether they are more permanent arrangements. Using data from the Household, Income and Labour Dynamics in Australia survey, it is estimated that 24% of the population aged 18 and over that is not cohabiting or married identify themselves as being in an intimate ongoing relationship. While non-residential unions are most prevalent among young people, they are experienced by individuals at all stages of the life course, including single parents and previously married people. While the younger generations frequently anticipate moving into a common residence with their partner in the future, among the older generations, living apart from a partner appears to be a more permanent arrangement, allowing for a combination of both intimacy and autonomy.
Keywords: Families and relationships; Families and relationships